A-site magnesium regulation for defect-optimized perovskite oxides toward efficient and durable alkaline oxygen evolution - Xintong Lv; Kaitao Li; Chengjun Xie; Zijun Xu; Feifei Dong; Yufei Ma; Zhan Lin (Fuel, 2026)

Negative Responses of Understory Plant Communities to Nitrogen and Phosphorus Enrichments in Forests: Tests From a Field Experiment and a Meta‐Analysis - Kai Dong; Suhui Ma; Wenjing Fang; Haojie Su; Danhua Zhang; Jiangling Zhu; Chengjun Ji; Zhang Zhou; Dexiang Chen; Tao Zhang; Biao Zhu; Jingyun Fang (Global Change Biology, 2026)
Anthropogenic nitrogen (N) and phosphorus (P) inputs have significant effects on plant community composition and diversity in forest ecosystems. Compared to canopy layers, understory communities are more sensitive to exogenous nutrient inputs. Although some experimental evidence exists on the effects of N addition on understory communities, knowledge about the impacts of P addition and its interaction with N, as well as the underlying mechanisms, remains limited. Here, we conducted two nutrient manipulation experiments in tropical primary and secondary montane rainforests, and synthesized 33 peer‐reviewed studies to evaluate the impacts of N and P enrichments on species richness, density, and cover of understory plants in forests. Integrated evidence from field experiments and meta‐analyses consistently demonstrated that nutrient enrichment with N, P, or both significantly reduced the species richness, density, and cover of understory plant communities. The negative impacts intensified with experimental duration and addition rate. Mechanistically, alteration in soil conditions including excessive accumulations of N and P as well as N‐induced soil acidification mainly caused the loss of understory plant species. Our study underscores the negative influences of anthropogenic nutrient inputs on understory community diversity and coverage, thereby altering forest structure and functioning in the future.

Hierarchical dual-crosslinked hydrogel electrolyte with quaternary ammonium and nanofiber reinforcement for durable and flexible zinc-ion batteries - Jiahui Li; Yaxin Wang; Chengxu Wang; Hao Wu; Sheng Li; Jing Ma; Jian Ni; Zhonglong Zhao; Xiaofang Jia; Fuhua Hou; Yanlai Wang; Chengjun Zhu; et al. (Chemical Engineering Journal, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

Livestock-induced changes in soil properties and microbial dominance determine soil microbial diversity in a conifer forest - Fan Fan; Jiangling Zhu; Kai Dong; Suhui Ma; Chengjun Ji; Zhiyao Tang; Shaopeng Wang; Xiaoli Shen; Sheng Li; Jingyun Fang (Soil Ecology Letters, 2026)

Effects of 13‐Year Nitrogen Additions on Stoichiometric Relationship in the Plant–Soil–Microbial Continuum From Tropical to Boreal Forests - Danhua Zhang; Zhengbin Yan; Di Tian; Suhui Ma; Kai Dong; Chen Yang; Chengjun Ji; Xuemei Yang; Chenhui Chang; Zixuan Wang; Changti Zhao; Jiangling Zhu; et al. (Global Change Biology, 2025)
Ecological stoichiometry in the plant–soil–microbial systems is crucial for regulating nutrient flow and sustaining ecosystem functions in forests. However, how rising atmospheric nitrogen (N) deposition induced by human activities impacts the stoichiometric relationships across ecosystem compartments remains poorly understood. We therefore conducted a 13‐year N‐addition experiment across eight forests from tropical to boreal zones in China, to assess the shifts in carbon:nitrogen:phosphorus (C:N:P) stoichiometry across live plant tissues, detritus, soil, and microbes. The N addition significantly elevated N concentrations in green leaves (+7.2% to 10.1%), twigs (+8.4%), fine roots (+20.2%), and leaf litter (+5.9%), while decreasing microbial N (−16.0%) and P concentrations (−20.2% to − 12.1%) across compartments. These changes triggered compartment‐specific responses, with greater stoichiometric variability in plants than in soils, particularly in high‐latitude forests. However, N addition did not significantly alter the intrinsic scaling relationships of P concentrations and N:P ratios among compartments or the N–P scaling patterns within individual compartments. Our findings provide new insights into the resilience and complexity of nutrient regulation in forests under chronic N deposition, with important implications for predicting long‐term ecosystem responses and developing sustainable nutrient management strategies.

Preparation and evaluation of licochalcone A - integrated casein-pectin nanodelivery system: Insights into its gastrointestinal digestibility and bioavailability - Mei Li; Shuang Yang; Huixiang Yi; Ziying Wang; Bo Xu; Gang Li; Chengjun Ma; Chengshan Yuan; Zhenhua Wang (Food Chemistry, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Dissolved organic matter derived from long-term photodegradation of plastics alters microbial methane conversion in mangrove sediments - Minmin Wang; Leiqian Ma; Derong Zhang; Fan Yang; Xing Yang; Bin Wang; Xue Li; Chengjun Ge; Jiwei Luo; Ying Zhang (Bioresource Technology, 2025)

Effects of nitrogen and phosphorus additions on soil particulate organic carbon through altering microbial decomposition in two tropical montane rainforests - Kai Dong; Zixin Chen; Suhui Ma; Xuemei Yang; Wenao Wu; Danhua Zhang; Chen Yang; Fan Fan; Jiangling Zhu; Chengjun Ji; Jingyun Fang (Plant and Soil, 2025)

Mechanism of improvement of the power conversion efficiency of Cu2ZnSn(S, Se)4 solar cells through changing Ag and Cd co-doping form from uniform to non-uniform - Mengge Li; Ding Ma; Bin Yao; Yongfeng Li; Zhanhui Ding; Chunkai Wang; Hongmei Luan; Chengjun Zhu (Chemical Engineering Journal, 2025)

Mycorrhizal association shapes responses of plant biomass but not soil carbon to nitrogen addition in global forests - Danhua Zhang; Suhui Ma; Xuemei Yang; Erhan Huang; Chen Yang; Kai Dong; Lingli Liu; Biao Zhu; Zhiyao Tang; Chengjun Ji; Jiangling Zhu; Jingyun Fang (Forest Ecology and Management, 2025)

Long-term nitrogen addition promotes soil acidity in two tropical montane rainforests - Kai Dong; Suhui Ma; Zhang Zhou; Lai Jiang; Danhua Zhang; Chen Yang; Zixin Chen; Chengjun Ji; Jiangling Zhu; Biao Zhu; Jingyun Fang (Soil Ecology Letters, 2025)

Field Experiments and a Meta‐Analysis Reveal a Minor Influence of Nitrogen Addition on Phosphorus Fractions in Forests - Qingshui Yu; Xiaofeng Ni; Frank Hagedorn; Josep Penuelas; Jordi Sardans; Mai‐He Li; Suhui Ma; Jianxiao Zhu; Di Tian; Chengyang Zheng; Jiangling Zhu; Chengjun Ji; et al. (Global Change Biology, 2025)
Anthropogenic nitrogen (N) inputs can significantly impact nutrient cycling and ecosystem functioning in terrestrial ecosystems. However, the effects of N addition on phosphorus (P) cycling processes in forest ecosystems remain unclear. In this study, we combined data from a long‐term (11‐year) N addition experiment across seven different forests ranging from temperate to tropical biomes, with a global meta‐analysis from 88 relevant publications, to investigate the responses of P cycling‐related variables to N inputs in forest ecosystems. We found that N addition had little effect on most P cycling‐related variables (e.g., leaf P, soil total P, soil available P, soil P fractions, and microbial biomass P) across the studied forest ecosystems. The meta‐analysis highlighted that N‐induced changes in P cycling were highly variable. Only a few variables, such as the leaf P concentration and the activity of soil acid phosphatase, presented significant responses to N addition and changed with climatic zone and the amount and duration of N inputs. Our study suggests that P cycling processes in forest ecosystems remain largely unaffected by N inputs. Our findings contribute to a better understanding and prediction of biogeochemical cycles in the context of N deposition related to anthropogenic activities and global climate change.

Soil nematode diversity depends on understory plant species richness in a subalpine forest - Suhui Ma; Yangang Li; Fan Fan; Wenjing Fang; Qiong Cai; Xinyu Xiong; Zhiming Zhang; Jiangling Zhu; Chengjun Ji (Applied Soil Ecology, 2025)

Determination of alkali metal elements in solid biomass fuel by laser-induced breakdown spectroscopy: Analysis and reduction of chemical matrix effects - Chengjun Li; Zhimin Lu; Jinzheng Chen; Ziyu Yu; Qi Yang; Huaiqing Qin; Xiwen Xing; Qingxiang Ma; Shunchun Yao (Analytica Chimica Acta, 2025)

Achieving high-efficiency Cu2ZnSn(S,Se)4 solar cells by Ag doping in Cu2ZnSn(S,Se)4 and substituting annealed In0.01Cd0.99S for CdS - Ding Ma; Mengge Li; Bin Yao; Yongfeng Li; Zhanhui Ding; Hongmei Luan; Chengjun Zhu; Jiayong Zhang; Chunkai Wang (Chemical Engineering Journal, 2025)

Nitrogen addition promotes soil carbon accumulation globally - Xuemei Yang; Suhui Ma; Erhan Huang; Danhua Zhang; Guoping Chen; Jiangling Zhu; Chengjun Ji; Biao Zhu; Lingli Liu; Jingyun Fang (Science China Life Sciences, 2025)

Mycorrhizal dominance influences tree species richness and richness–biomass relationship in China's forests - Suhui Ma; Guoping Chen; Qiong Cai; Chengjun Ji; Biao Zhu; Zhiyao Tang; Shuijin Hu; Jingyun Fang (Ecology, 2025)
Mycorrhizal associations drive plant community diversity and ecosystem functions. Arbuscular mycorrhiza (AM) and ectomycorrhiza (EcM) are two widespread mycorrhizal types and are thought to differentially affect plant diversity and productivity by nutrient acquisition and plant–soil feedback. However, it remains unclear how the mixture of two mycorrhizal types influences tree diversity, forest biomass, and their relationship at large spatial scales. Here, we explored these issues using data from 1247 plots (600 m 2 for each) across China's natural forests located mostly in temperate and subtropical regions. Both AM‐dominated and EcM‐dominated forests show relatively lower tree species richness and stand biomass, whereas forests with the mixture of mycorrhizal strategies sustain more tree species and higher biomass. Interestingly, the positive effect of tree diversity on biomass is stronger in forests with low (≤50%) than high AM tree proportion (>50%), reflecting a shift from the complementarity effect to functional redundancy with increasing AM trees. Our findings suggest that mycorrhizal dominance influences tree diversity and richness–biomass relationship in forest ecosystems.

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Experimental and numerical investigation on deck system of a 102 m simply supported prestressed UHPC box-girder highway bridge - Sui Luo; Hua Zhao; Dongqin Qiao; Chengjun Tan; Xudong Shao; Jing Ma; Huangguo Qian; Zhilian Liao; Zhentao Hu; Cuizhu Zhou (Engineering Structures, 2024)

Concept and flexural performance of non-prestressed steel plate-UHPC-NC composite girder bridge - Lei Tu; Hua Zhao; Dongqin Qiao; Junde Hu; Chengjun Tan; Jing Ma; Zhentao Hu; Huiren Qiu; Xudong Shao (Engineering Structures, 2024)

Practical four-electron zinc-iodine aqueous batteries enabled by orbital hybridization induced adsorption-catalysis - Tingting Liu; Chengjun Lei; Huijian Wang; Chen Xu; Wenjiao Ma; Xin He; Xiao Liang (Science Bulletin, 2024)

Evaluation of characteristics on the indoor dwelling environments of traditional villages in Hehuang area of China based on basic environmental parameters under remote sensing technology - Hongbin Ma; Chengjun Jing; Ang Hu; Lihua Ma (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Life-cycle profiling of cuticular hydrocarbons in the cotton bollworm Helicoverpa armigera (Lepidoptera: Noctuidae) - Chengjun Ma; Yucui Xin; Ruoyao Ni; Mei Li; Xinghui Qiu (Journal of Asia-Pacific Entomology, 2024)

Positive effects of vegetation restoration on the soil properties of post-mining land - Cuihuan Li; Yongkang Ji; Nan Ma; Jing Zhang; Hui Zhang; Chengjun Ji; Jiangling Zhu; Junjiong Shao; Yan Li (Plant and Soil, 2024)

Astronomical Time Scale of the Late Pleistocene in the Northern South China Sea Based on Carbonate Deposition Record - Chunhui Zhang; Wanyi Zhang; Chengjun Zhang; Liwei Zheng; Shiyi Yan; Yuanhao Ma; Wei Dang (Journal of Marine Science and Engineering, 2024)
Variations in solar insolation caused by changes in the Earth’s orbit—specifically its eccentricity, obliquity, and precession—can leave discernible marks on the geologic record. Astrochronology leverages these markers to establish a direct connection between chronological measurements and different facets of climate change as recorded in marine sediments. This approach offers a unique window into the Earth’s climate system and the construction of high-resolution, continuous time scales. Our study involves comprehensive bulk carbonate analyses of 390 discrete samples from core SCS1, which was retrieved from the deep-sea floor of the northern South China Sea. By utilizing carbonate stratigraphic data, we have developed a carbonate stratigraphic age model. This was achieved by aligning the carbonate sequence from core SCS1 with the established carbonate standard stratigraphic time scale of the South China Sea. Subsequently, we construct an astronomically tuned time scale based on this age model. Our findings indicate that sediment records in this core have been predominantly influenced by a 20,000-year cycle (precession cycle) throughout the Late Pleistocene. We have developed an astronomical time scale extending back approximately 110,000 years from the present, with a resolution of 280 years, by tuning the carbonate record to the precession curve. Time-domain spectral analysis of the tuned carbonate time series, alongside the consistent comparability of the early Holocene low-carbonate event (11–8 kyr), underscores the reliability of our astronomical time scale. Our age model exposes intricate variations in carbonate deposition, epitomizing a typical “Pacific-type” carbonate cycle. Previous research has illustrated that precession forcing predominantly influences productivity changes in the South China Sea. The pronounced precession-related cycle observed in our record suggests that changes in productivity significantly impact carbonate content in the area under study. Furthermore, the clear precession period identified in the carbonate record of core SCS1 reflects the response of low-latitude processes to orbital parameters, implying that carbonate deposition and preservation in core SCS1 are chiefly influenced by the interplay between the Intertropical Convergence Zone (ITCZ) and the monsoon system within the precession band. Our astronomical time scale is poised to enhance paleoceanographic, paleoclimatic, and correlation studies further. Additionally, the independent evidence we provide for using proxy records for astronomical age calibration of marine sediments lends additional support to similar methods of astronomical tuning.

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Facile synthesis of multi-layer Co(OH)2/CeO2-g-C3N4 ternary synergistic heterostructure for efficient photocatalytic oxidation of NO under visible light - Zhiyu Xiao; Hainam Do; Abubakar Yusuf; Hongpeng Jia; Haolun Ma; Shanshan Jiang; Jianrong Li; Yong Sun; Chengjun Wang; Yong Ren; George Zheng Chen; Jun He (Journal of Hazardous Materials, 2024)

Porous polypyrrole Nanotube-Based Organohydrogels: Versatile materials for robust electromagnetic interference shielding in harsh environments - Lingsai Meng; Shuo Yang; Yu Ma; Yupeng Zou; Yang Zhang; Gang Chen; Chengjun Dong; Hongtao Guan (Chemical Engineering Journal, 2024)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

Nutritional Profile and Bioremediation of Tropical Marine Aquaculture with an Integrated Microalgae and Bacteria Symbiosis - Ruiyang Ma; Shiyu Xie; Huiting Jia; Linhai Pu; Licheng Peng; Chengjun Ge (Water, Air, & Soil Pollution, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

Progresses and emerging trends of arsenic research in the past 120 years - Chengjun Li; Jiahui Wang; Bing Yan; Ai-Jun Miao; Huan Zhong; Wei Zhang; Lena Qiying Ma (Critical Reviews in Environmental Science and Technology, 2021)

Effects of plant coverage on shrub fertile islands in the Upper Minjiang River Valley - Laiye Qu; Zhongbin Wang; Yuanyuan Huang; Yuxin Zhang; Chengjun Song; Keming Ma (Science China Life Sciences, 2018)

Retraction Note to: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2016)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Widespread decreases in topsoil inorganic carbon stocks across C hina's grasslands during 1980s–2000s - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Wenhong Ma; Anwar Mohammat; Shifeng Wang; Shaopeng Wang; Arindam Datta; David Robinson; Pete Smith (Global Change Biology, 2012)
Soil carbon (C) stocks consist of inorganic and organic components, ~1.7 times larger than the total of the C stored in vegetation and the atmosphere together. Significant soil C losses could thus offset any C sink in vegetation, creating a positive feedback to climate change. However, compared with the susceptible sensitivity of organic matter decay to climate warming, soil inorganic carbon ( SIC ) stocks are often assumed to be relatively stable. Here, we evaluated SIC changes across C hina's grasslands over the last two decades using data from a recent regional soil survey during 2001–2005 and historical national soil inventory during the 1980s. Our results showed that SIC stocks in the top 10 cm decreased significantly between the two sampling periods, with a mean rate of 26.8 (95% confidence interval : 15.8–41.7) g C m −2 yr −1 . The larger decreases in SIC stocks were observed in those regions with stronger soil acidification and richer soil carbonates. The lost SIC could be released to the atmosphere as carbon dioxide, redistributed to the deeper soil layer, and transferred to the nearby regions. The fraction of soil carbonates entering into the atmosphere may diminish the strength of terrestrial C sequestration and amplify the positive C‐climate feedback.

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Significant soil acidification across northern China's grasslands during 1980s–2000s - Yuanhe Yang; Chengjun Ji; Wenhong Ma; Shifeng Wang; Shaopeng Wang; Wenxuan Han; Anwar Mohammat; David Robinson; Pete Smith (Global Change Biology, 2012)
Anthropogenic acid deposition may lead to soil acidification, with soil buffering capacity regulating the magnitude of any soil pH change. However, little evidence is available from large‐scale observations. Here, we evaluated changes in soil pH across northern China's grasslands over the last two decades using soil profiles obtained from China's Second National Soil Inventory during the 1980s and a more recent regional soil survey during 2001–2005. A transect from the central‐southern Tibetan Plateau to the eastern Inner Mongolian Plateau, where Kriging interpolation provided robust predictions of the spatial distribution of soil pH , was then selected to examine pH changes during the survey period. Our results showed that soil pH in the surface layer had declined significantly over the last two decades, with an overall decrease of 0.63 units (95% confidence interval = 0.54–0.73 units). The decline of soil pH was observed in both alpine grasslands on the Tibetan Plateau and temperate grasslands on the Inner Mongolian Plateau. Soil pH decreased more intensively in low soil carbonate regions, while changes of soil pH showed no significant associations with soil cation exchange capacity. These results suggest that grassland soils across northern China have experienced significant acidification from the 1980s to 2000s, with soil carbonates buffering the increase in soil acidity. The buffering process may induce a large loss of carbon from soil carbonates and thus alter the carbon balance in these globally important ecosystems.

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)